Job crafting - Zhang, Fangfang; Parker, Sharon (2022)
It is difficult and sometimes impossible for organizations to design jobs that fit all employees due to increased complexity and uncertainty in the workplace. Scholars have proposed that employees can make changes to their jobs themselves by engaging in job crafting. Job crafting is defined as self-initiated change that employees make in their work to better fit their abilities, needs, and preferences. Employees can craft their jobs individually and collaboratively, as a team. Two main theoretical perspectives have been proposed, which are distinct in how they define job crafting. The application of these two job crafting perspectives has brought some confusion about the construct of job crafting and how it is measured, and has resulted in some challenges in synthesizing empirical studies. To reduce this confusion, scholars have integrated the two distinct job crafting paper; we begin by introducing the definitions and measurements of individual job crafting and team job crafting. Specifically, theories of job crafting are reviewed from two perspectives using three distinct categorizations, with approach crafting versus avoidance crafting identified as the most important. A great number of empirical studies have been conducted to investigate the consequences of job crafting and factors that affect it. Systematic reviews and meta-analyses have shown positive effects of approach job crafting for employees, such as increased job satisfaction, motivation, work engagement, organizational commitment, and job performance, and decreased strain and turnover intentions. However, avoidance crafting has been associated with burnout and lowered job performance. Organizational factors and individual factors that affect individual job crafting have been identified, including job autonomy, organizational support, leadership, proactive personality, self-efficacy, and regulatory focus. Beyond antecedents and outcomes of job crafting that have been systematically reviewed in the literature, studies on job crafting have also (a) empirically tested the interrelationships of different job crafting constructs, (b) uncovered new forms of job crafting, (c) unraveled the complicated effects of job crafting, (d) unpacked the influences of social context in job crafting process and outcomes, (e) considered job crafting in different populations and contexts, (f) investigated the effect of cultural differences on job crafting, and (g) investigated antecedents and outcomes of team job crafting. Finally, evidence has shown that job crafting behaviors can be trained: intervention studies show the effectiveness of job crafting interventions in stimulating job crafting behaviors and related positive outcomes such as well-being, engagement, and performance.